The Dynamics Of Impulse And Control In Generation Z’s Financial Well-Being: Dinamika Impuls Dan Kontrol Dalam Kesejahteraan Keuangan Generasi Z - Amanda Dwi Kurnia; Salsabella Nur Ikhsaniyah; Maharani Zuroida; Aldi Saputro; Irwan Adimas Ganda Saputra (Universitas Negeri Yogyakarta, 2026)
Generation Z is entering adulthood, which is why their status as digital natives exposes them to high online distractions, particularly the fear of missing out (FOMO). Recent data shows that 77% of Generation Z purchasing decisions are influenced by social media, so this study aims to evaluate the effect of FOMO and financial knowledge on financial well-being with self-control as a moderating variable. An online questionnaire, 322 Gen Z respondents were selected using the Hair formula. Data were analyzed by path analysis through SmartPLS 4.0. The results suggest noteworthy impacts of both FOMO and financial well-being (FWB) on this demographic, such that while each factor contributes to explaining individual financial well-being, only one of them acts as a moderator. The variance in financial well-being explained by this model is the 61.9% with an acceptable data fit. FOMO can be a motivator to seize financial opportunities. Overall, this study deepens the insight into financial behavior by providing a brief overview of both sides of FOMO in the digital world, and incorporating self-control as a psychological filter when making financial decisions.